Problematizações e perspectivas curriculares na educação de alunos com altas habilidades/superdotação - Negrini, Tatiane (2015)
This dissertation is linked to the Doctorate Course in Education of the Post-Graduate Program in Education of the Federal University of Santa Maria and is part of the Research Line LP3 Special Education. The education of students with high abilities/gifted is an exciting matter considering the challenges that the schools nowadays possess. Thus, the overall objective proposed in this study is to investigate how the school curriculum has been constituted in order to meet the educational needs of these students, proposing, based on this, educational strategies for them. From a qualitative approach in educational research, this research is characterized as a case study in a public school in the city of Santa Maria/Rio Grande do Sul, Brazil. Documentary analysis was performed as well as field collection with semi-structured narrative interviews. The subjects of the study were students with high abilities/gifted, their teachers (from the resource class and regular class) and a member of the teaching coordination of the studied school. From the theoretical study which underlies this study and the collected data, categories were chosen to perform the analysis, based on the assumptions of Content Analysis (BARDIN, 2011). It is understood that the school curriculum has been creating educational possibilities for students with high abilities/gifted. In addition, the narratives show concern teachers regarding this aspect. However, the teaching practices still require qualification, whether they are of intra or extracurricular enrichment, with curriculum strategies differentiated to this public. Considering the theoretical studies and the analysis performed, the proposed objectives were achieved, and was suggested the spiral curriculum perspectives in order to propose curricular alternatives to reflect on the educational services to such students.